ParSCo: celebrating 10 years of a unique parasitology summer course - Dantas-Torres, Filipe; Bezerra-Santos, Marcos Antonio; Mendoza-Roldan, Jairo Alfonso; Lia, Riccardo Paolo; Perles, Livia; Barrera, Juan Pedro; Fagundes-Moreira, Renata; Carbonara, Mariaelisa; Varcasia, Antonio; Brianti, Emanuele; Deak, Georgiana; Rojas, Alicia; et al. (Parasites & vectors, 2024)
ParSCo (Parasitology Summer Course) is an intense, 1-week-long summer course organized by the Parasitology Unit of the Department of Veterinary Medicine, University of Bari, Italy, with the support of the World Association for the Advancement of Veterinary Parasitology (WAAVP), the European Veterinary Parasitology College (EVPC) and Parasites and Vectors. The course, which is conducted in southern Italy, is planned for parasitologists and post-graduate students working in the field of parasitology. The course consists of theoretical and practical lessons, which include the collection, identification and diagnosis of parasites of pets, livestock and wildlife. The participants in ParSCo are afforded the opportunity to be involved in clinical examination and sample collection for the diagnosis of parasitic diseases (e.g. leishmaniosis, thelaziosis and many tick-borne diseases) present in the Mediterranean Basin. The course is conducted at Casa di Caccia, a hunting lodge situated in the Gallipoli Cognato Forest near the Basento River in the Basilicata region in southern Italy. In addition to the training purpose, ParSCo is a great opportunity for sharing knowledge and expertise while becoming part of the parasitology community in a pleasant environment. In this editorial, we share some information and celebrate 10 years of ParSCo, looking forward to forthcoming sessions of this unique parasitology summer course.
Keywords: Parasitic Diseases, Animal; Animals, Wild; dobytek; Itálie; Animals; divoká zvířata; Humans; Students; Italy; parazitární nemoci u zvířat; lidé; zvířata; Livestock; Parasitology; parazitologie; studenti